Peran Influencer di Media Sosial terhadap Minat Beli Produk Sunscreen Azarine (5) - Mu minah, Afifah; Jannah, Gina Raudhatul; Fadhlurahman, Nawaal; Al Isyvani, Rawza (Universitas Haji Sumatera Utara, 2024)
Marketing a product on social media is less effective without the role of influencers. However, many influencers who provide reviews are not by the reality of the product and the personal branding of the influencer. The purpose of this study is to determine the effectiveness of marketing with influencers on social media on public buying interest in Azarine sunscreen products. This research uses a descriptive qualitative method with a questionnaire survey through Google Forms. Consumer trust and buying interest in Azarine sunscreen products can be increased by marketing through influencers. This research clarifies how important it is to align the real quality of the product with the personal branding of an influencer, to build trust and increase consumer buying interest effectively. The results of this study show that influencers have an important role in improving the purchase intention of a product with honest and transparent content. This research shows that marketing strategies through influencers can increase consumer trust and buying interest in Azarine sunscreen products if the reviews given are by the reality of the product quality.